PENGARUH EARNING PER SHARE DAN VOLUME PERDAGANGAN SAHAM TERHADAP RETURN SAHAM - Jaelani, Ihrom; Feriansah, Rival; Saputra, Adi (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2025)
This study aims to analyze the effect of earnings per share (EPS) and trading volume on stock returns of Islamic banks listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The study employed a quantitative approach with descriptive and verification methods. The sample was determined using a purposive sampling technique with BRIS, BTPS, PNBS, and ARTO stocks as the research objects. The data used were secondary data obtained from financial reports and IDX stock market data. Data analysis techniques included multiple linear regression analysis, t-test, F-test, correlation coefficient, and coefficient of determination. The results showed that EPS and trading volume, both partially and simultaneously, had a positive and significant effect on stock returns of Islamic banks.